2020
DOI: 10.3390/ijerph17176412
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Driving Study in Brazil: An Analysis of Mobile Phone Use Behavior while Driving

Abstract: Mobile phone use (MPU) while driving is an important road safety challenge worldwide. Naturalistic driving studies (NDS) emerged as one of the most sophisticated methodologies to investigate driver behavior; however, NDS have not been implemented in low- or middle-income countries. The aim of this research is to investigate MPU while driving and compare the results to those reported in international studies. An analysis of 61.32 h and 1350 km driven in Curitiba (Brazil) showed that MPU lasted for an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
0
14
0
3
Order By: Relevance
“…From the point of view of traffic safety, distracted behavior of using a smart phone among road users (e.g., drivers, motorcyclists, pedestrians) has concerned the researchers and practitioners. According to the evidence from a naturalistic driving study in Brazil [10], mobile phone use occurred in 58.71% of the driving trips (n = 201), indicating an average frequency of 8.37 interactions per hour. The time of using a mobile phone averagely accounted for 7.03% of the trip time, while calling/voice message (14.46%) and texting (7.39%) made up 21.85% of the total usage time.…”
Section: Drivers and Mobile Phone Distractionmentioning
confidence: 99%
“…From the point of view of traffic safety, distracted behavior of using a smart phone among road users (e.g., drivers, motorcyclists, pedestrians) has concerned the researchers and practitioners. According to the evidence from a naturalistic driving study in Brazil [10], mobile phone use occurred in 58.71% of the driving trips (n = 201), indicating an average frequency of 8.37 interactions per hour. The time of using a mobile phone averagely accounted for 7.03% of the trip time, while calling/voice message (14.46%) and texting (7.39%) made up 21.85% of the total usage time.…”
Section: Drivers and Mobile Phone Distractionmentioning
confidence: 99%
“…Besides its convenience and benefits mentioned above, inappropriate use of the device may also cause negative effects to their users. Specific to traffic scenarios, it is well established that drivers who engage in mobile phone use while driving would experience a higher level of risk, and driving performance would be significantly compromised [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the authors’ knowledge, very limited studies on this topic were carried out in a sample of Chinese population. In addition, previous studies demonstrated that traffic behavior might differ across countries due to the differences in culture, socio-economic factors and user habits [ 15 ]. Consequently, the utility of TPB for a Chinese sample is possibly different from the results reported in existing research conducted in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Conforme apontado por Bastos et al (2020), no ano de 2019 foi conduzida no Brasil uma iniciativa inédita de realizar um Estudo Naturalístico de Segurança Viária com base nas experiências internacionais já realizadas, equipando veículos e condutores com câmeras e receptores GPS, de forma a monitorar o trajeto, velocidades e ambiente viário no qual os carros estavam inseridos. Resultados a respeito do uso do telefone celular ao volante já foram publicados emBastos et al (2020). Tal metodologia de estudo se justifica mediante uma falta de pesquisas de campo pretéritas que envolvam o condutor brasileiro dentro de uma situação real de trânsito onde se analisam variáveis como as velocidades praticadas e suas relação com outros condutores e o ambiente ao seu redor, identificando ações que possam contribuir para a segurança viária.Dentro das possibilidades que se apresentam da coleta de dados de um estudo naturalístico, optou-se neste documento por investigar a relação da geometria de interseções urbanas com a velocidade praticada por veículos de passeio na cidade de Curitiba.…”
unclassified
“…As sessões de grupo focal realizadas no escopo do presente trabalho tiveram como objetivo reconhecer o perfil de condutores voluntários participantes do primeiro estudo naturalístico de segurança viária desenvolvido no Brasil, no qual foram investigados fatores comportamentais por meio do monitoramento da tarefa real de condução utilizando camêras e GPS embarcados. Uma descrição mais detalhada desta pesquisa pode ser encontrada emBastos et al (2020) e Valeixo e Suguinoshita(2020). STPR houve uma distribuição quase uniforme entre as faixas etárias, entretanto, de forma individual o grupo de condutores habituais apresentou uma idade média menor que os outros dois.…”
unclassified